Historiografi Gereja-gereja Lokal di Indonesia: Urgensi Preservasi Arsip-arsip dan Penulisan Sejarah Gereja- gereja Lokal - Sembiring, William Wahyu (Theologia in Loco, 2025)
Local churches in Indonesia hold a rich deposit of theological and historical memory rooted in the founding faith experiences of their communities, yet this deposit is under threat due to limited institutional awareness and capacity for preservation. At the same time, scholarly engagement with the historiography of local Indonesian churches — particularly work that offers a directly applicable methodological framework — remains scarce in the literature of Indonesian Christian theology and history. This article aims to construct a theoretical and practical foundation for local churches in Indonesia to undertake archival preservation and begin writing their church histories in a systematic manner. Drawing on a literature review and conceptual analysis, the article argues that local churches bear a theological and historical responsibility to save and preserve their memories (saving memories), and that this responsibility can be fulfilled through two complementary methodological approaches: formal history and pluralistic historiography. These findings indicate that the application of both approaches enables local churches not only to conserve past memory but also to transform it into historical narrative that contributes to a richer understanding of the development of Christianity in Indonesia.